LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK PSIKODRAMA UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA KELAS XI SMKN 6 GARUT - Fitrie Megianti; Heris Hendriana; Wiwin Yuliani (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
This research is motivated by the fact that there are still students who have low self-confidence in school. The form of efforts made in counseling guidance services to provide students' understanding in increasing self-confidence is through group guidance services. This research was conducted with a qualitative descriptive research approach that combines three ways of collecting data, namely observation, interviews and documentation. The research sample was 7 students of class XI at SMK Negeri 6 Garut. From the research that has been done, it is found that students feel better than the level of self-confidence with group guidance services and psychodrama techniques that researchers do. So it can be concluded that the technique used by the researcher can be one way to increase self-confidence, especially for students at school.Keywords: Self-confidence, group guidance services, Psychodrama Techniques, Learners.